Antigen-specific oncolytic MV-based tumor vaccines through presentation of selected tumor-associated antigens on infected cells or virus-like particles. Issue 1 (December 2017) - Hutzler, Stefan; Erbar, Stephanie; Jabulowsky, Robert; Hanauer, Jan; Schnotz, Jürgen; Beissert, Tim; Bodmer, Bianca; Eberle, Regina; Boller, Klaus; Klamp, Thorsten; Sahin, Ugur; Mühlebach, Michael
Abstract Recombinant vaccine strain-derived measles virus (MV) is clinically tested both as vaccine platform to protect against other pathogens and as oncolytic virus for tumor treatment. To investigate the potential synergism in anti-tumoral efficacy of oncolytic and vaccine properties, we chose Ovalbumin and an ideal tumor antigen, claudin-6, for pre-clinical proof of concept. To enhance immunogenicity, both antigens were presented by retroviral virus-like particle producedin situ during MV-infection. All recombinant MV revealed normal growths, genetic stability, and proper expression and presentation of both antigens. Potent antigen-specific humoral and cellular immunity were found in immunized MV-susceptible IFNAR−/− -CD46Ge mice. These immune responses significantly inhibited metastasis formation or increased therapeutic efficacy compared to control MV in respective novelin vivo tumor models using syngeneic B16-hCD46/mCLDN6 murine melanoma cells. These data indicate the potential of MV to trigger selected tumor antigen-specific immune responses on top of direct tumor lysis for enhanced efficacy.